PEMBERDAYAAN KETERAMPILAN PENEMUAN DALAM SCIENTIFIC APPROACH MELALUI PEMBELAJARAN BERBASIS REMAP COOPLE - Zubaidah, Siti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The various studies indicated that our students have low reading habit, academics achievement, social attitudes, and many other skills. The kinds of skills that need to be empowered are the five discovery skills owned by the inovators in the world, ie associating, questioning, observing, experimenting, and networking. In the curriculum of 2013, those five discovery skills are packages in the scientific approach. Those five skills can be taught to students with remap coople based learning, through reading assignments then making concept map, and the learning is done by the models of cooperative learning. The remap coople based learning have been examined by several studies and the results showed there were improvement in some aspects observed. This paper will discuss the short review about the five discovery skills, scientific approach, and remap coople based learning.Â Keywords: discovery skills, scientific approach, remap coople